Digital economy: terminological discourse - U. Yu. Blinova; N. K. Rozhkova; D. Yu. Rozhkova (Вестник университета)
Due to the frequent use of the terms “digital economy”, “digitalisation” and “digital transformation” in regulation legal documents and methodological developments concerning the information technologies development and implementation in society and the economy, it is relevant to analyse the essence and application of these definitions. A terminological analysis of these concepts was carried out, and attention to main practical aspects describing these phenomena is paid in the article. A significant terminological discrepancy in these concepts in legislative documents, research and practice was noted. This leads to the emergence of incorrect messages for the methodological and practical conclusions both on a global scale and at the specific economic actors level. A logical scheme of interaction and interpenetration of the processes, arising in the digital economy creation, digitalisation and digital transformation, was built, which has allowed to create the authors’ vision of the definitions essence for their further use in science and practice.